Monoclonal antibodies to the guanine-nucleotide binding proteins of adenylate cyclase. - Lingham, R B (1986)
Monoclonal antibodies (Mabs) to the stimulatory (Ns) and inhibitory (Ni) guanine nucleotide regulatory proteins associated with adenylate cyclase have been developed. Two Mabs (2A3 and 5G12), which are of the IgG2b subclass, recognize the beta-subunits (beta) of Ns, Ni and transducin. Iodinated beta can be immunoprecipitated by either Mab coupled to Affi-Gel 10 and this can be decreased by prior incubation of the Mabs with excess unlabelled beta. The Mabs stabilize the activated state of Ns while decreasing the rate of deactivation of activated Ns in the presence of beta.